2009
DOI: 10.1124/mol.109.059139
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Specific Differences in Corticotropin-Releasing Factor Receptor Complexes Detected by Fluorescence Spectroscopy

Abstract: G protein-coupled receptors have been proposed to exist in signalosomes subject to agonist-driven shifts in the assembly disassembly equilibrium, affected by stabilizing membrane lipids and/or cortical actin restricting mobility. We investigated the highly homologous corticotropin-releasing factor receptors (CRFRs), CRFR1 and -2, which are different within their hydrophobic core. Agonist stimulation of CRFR1 and CRFR2 gave rise to similar concentration-response curves for cAMP accumulation, but CRFR2 underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
(60 reference statements)
3
25
1
Order By: Relevance
“…3) Our result that the M/D of the CRF 1 R remains constant upon receptor activation is consistent with previous suggestions for this receptor using FRET experiments (29,30). This result may be specific for the CRF 1 R. However, the recently published smTIRFM studies for the N-formyl peptide receptor (25) and the ␤1-and ␤2-adrenergic receptors (26) also showed that the M/Ds of these receptors are unaffected by receptor activation.…”
Section: Gpcrssupporting
confidence: 81%
See 3 more Smart Citations
“…3) Our result that the M/D of the CRF 1 R remains constant upon receptor activation is consistent with previous suggestions for this receptor using FRET experiments (29,30). This result may be specific for the CRF 1 R. However, the recently published smTIRFM studies for the N-formyl peptide receptor (25) and the ␤1-and ␤2-adrenergic receptors (26) also showed that the M/Ds of these receptors are unaffected by receptor activation.…”
Section: Gpcrssupporting
confidence: 81%
“…Such a codiffusion would lead to a strong increase in diffusion time, which was not observed in our experiments. The detected diffusion times were consistent with the literature (30), and the cross-correlation amplitudes derived from the FCCS experiments thus only reflect receptor interactions. In the case of the FCCS measurements at the ER membrane, however, we observed in some experiments an increase in diffusion time to a certain extent.…”
Section: Selection Cloning Expression and Subcellular Location Of supporting
confidence: 76%
See 2 more Smart Citations
“…Likewise, Pontier et al (2008) proposed that ␤ 2 -adrenergic receptors did not partition within the liquid-ordered lipid phase, whereas G-proteins and adenylyl cyclases were sequestered in these domains, and that their mobilization led to increased receptor-mediated signaling. Milan-Lobo et al (2009) suggested, on the basis of FRET and FRAP studies, that the restricted mobility of corticotropin-releasing factor receptors (CRFR2) may be increased by agonist activation of the receptors, suggesting a transfer into a different membrane compartment or loss of contact with the cytoskeleton.…”
mentioning
confidence: 99%